The Tripartite Realist War: Analysing Russia's Invasion of Ukraine - Singh, Danny (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
"Danny Singh's latest book provides a timely analysis of the war in Ukraine. Drawing on detailed political history of the region and theories of international relations, he maintains that the realist doctrine of self-interest on the part of state actors best explains the major decisions made by Ukraine, Russia, and NATO, while liberal idealism explains little. Singh hopes that an accurate account of why the war was begun would help it come to an end." -Thaddeus Metz, University of Pretoria, Pretoria "Danny Singh offers a persuasive, multi-layered exploration that makes for great reading. It is a compelling, fresh, and fascinating text. Singh has done the international community a service by offering an account with a remarkable balance, which is exactly what is badly missing right now." - Georgios A. Antonopoulos, Northumbria University, Newcastle The book offers a detailed analysis on Russia's invasion of Ukraine. A book needs to be written on this to make sense, from a theoretical perspective, why this invasion has occurred and what the main actors are pursuing. The originality rests on testing main international relations theories: realism, liberalism and constructivism to the war that emerges with the practices and approaches during the Cold War to date from the North Atlantic Treaty Organisation (NATO), the Soviet Union (and now Russia) and Ukraine. The monograph commences with a historical overview of NATO and how it has engaged in expansionism policy to further contain Russia in contemporary international affairs with the accession of additional former Soviet states. This helps to explain the current Russian invasion of Ukraine that would attract great readership. The main argument presented rests on the pursuance of realist interests by NATO, Ukraine and Russia for containment, national security interests and as a response to the security dilemma respectively. This has served as the main catalyst of this conflict that has made diplomacy, international law and collective security measures problematic to implement. Danny Singh is Senior Lecturer in Politics and International Relations at Teesside University, UK.
Chapter.1 Introduction -- Chapter 2. Main International Relations Theories -- Chapter 3. NATO During the Cold War and Dissolution of the Soviet Union -- Chapter 4. Ukrainian Desire for Political Autonomy and NATO Accession -- Chapter 5. Russian Responses, the Invasion, Sanctions and International Law -- Chapter 6. Conclusion.
Keywords: International relations; Security, International; International Relations Theory; International Security Studies